Combined effects of fatigue and surface instability on jump biomechanics in elite athletes - Prieske, O.; Demps, M.; Lesinski, M.; Granacher, U. (International Journal of Sports Medicine, 2017)
The present study aimed to examine the effects of fatigue and surface instability on kinetic and kinematic jump performance measures. Ten female and 10 male elite volleyball players (18±2 years) performed repetitive vertical double-leg box jumps until failure. Pre and post fatigue, jump height/performance index, ground reaction force and knee flexion/valgus angles were assessed during drop and countermovement jumps on stable and unstable surfaces. Fatigue, surface condition, and sex resulted in significantly lower drop jump performance and ground reaction force (p=0.031, 1.1=d=3.5). Additionally, drop jump knee flexion angles were significantly lower following fatigue (p=0.006, d=1.5). A significant fatigue×surface×sex interaction (p=0.020, d=1.2) revealed fatigue-related decrements in drop jump peak knee flexion angles under unstable conditions and in men only. Knee valgus angles were higher on unstable compared to stable surfaces during drop jumps and in females compared to males during drop and countermovement jumps (p=0.054, 1.0=d=1.1). Significant surface×sex interactions during countermovement jumps (p=0.002, d=1.9) indicated that knee valgus angles at onset of ground contact were significantly lower on unstable compared to stable surfaces in males but higher in females. Our findings revealed that fatigue and surface instability resulted in sex-specific knee motion strategies during jumping in elite volleyball players.